Promoting Sustainable Development Goal 5 through Ubuntu-Based South African Basic Education Curriculum: - Sulaimon Adewale (Indonesia Approach Education, 2023)
Gender inequality is a pervasive problem worldwide, and achieving Sustainable Development Goal 5 (SDG 5) of gender equality is crucial for social progress. In South Africa, gender disparities persist in primary and secondary education, hindering girls' access to quality education and opportunities. This study explores the application of the Ubuntu socio-cultural principle in addressing SDG 5 in South Africa. Ubuntu, an African philosophy emphasizing interconnectedness and humaneness, offers insights into fostering social justice and equality. By integrating Ubuntu principles into education, South African secondary schools can promote inclusive classrooms, gender sensitization programs, peer support, and mentorship. Inclusive education ensures equal participation and opportunities for all students, fostering respect for diversity. Gender sensitization programs raise awareness, challenge stereotypes, and promote empathy and understanding. Peer support and mentorship programs create a supportive network, breaking gender barriers and fostering positive role modeling. Applying Ubuntu principles in South African secondary schools can contribute to achieving SDG 5 by creating an inclusive and respectful educational environment that values and respects all students, regardless of gender. By promoting empathy, understanding, and collective responsibility, Ubuntu can help challenge harmful gender norms and foster dialogue, collaboration, and transformative change towards gender equality.